2009
DOI: 10.1532/hsf98.20081116
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nonlinear Heart Rate Dynamics after Beating-Heart Revascularization

Abstract: The decreases in alpha1, average FD, and high FD indicate that a profound decay of cardiac complexity and fractal correlation can be observed after off-pump CABG. Furthermore, a more extensive impairment of nonlinear indices was observed in patients who developed postoperative arrhythmias than in those who remained in stable sinus rhythm. Our findings suggest that the postoperative hyperadrenergic setting acts as a preliminary condition in which both reduced and enhanced vagal activity may predispose patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
3
18
2
Order By: Relevance
“…In the light of these findings the preoperative values of τ(q¼2), τ(q¼3) and h_top parameters in the current study indicate that a marked decay of multifractal behavior occurred already preoperatively in our patients, clearly showing that in these individuals a cardiac autonomic disbalance with a sympathetic predominance existed already prior to the surgical intervention. Such results are in accord with previous studies as well as with our own observations reporting on diminished linear and selected nonlinear HRV parameters in older patients with stable multivessel coronary artery disease [1][2][3][4]14,15]. Since the Δh parameter is known to strongly correlate also with the sympathetic activity, a higher preoperative values of parameter Δh in our group as compared to healthy subjects might suggest that the preoperative sympathovagal disbalance in our patients can be mainly attributed to sympathetic overdrive and to a lesser degree to parasympathetic decrement [24].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the light of these findings the preoperative values of τ(q¼2), τ(q¼3) and h_top parameters in the current study indicate that a marked decay of multifractal behavior occurred already preoperatively in our patients, clearly showing that in these individuals a cardiac autonomic disbalance with a sympathetic predominance existed already prior to the surgical intervention. Such results are in accord with previous studies as well as with our own observations reporting on diminished linear and selected nonlinear HRV parameters in older patients with stable multivessel coronary artery disease [1][2][3][4]14,15]. Since the Δh parameter is known to strongly correlate also with the sympathetic activity, a higher preoperative values of parameter Δh in our group as compared to healthy subjects might suggest that the preoperative sympathovagal disbalance in our patients can be mainly attributed to sympathetic overdrive and to a lesser degree to parasympathetic decrement [24].…”
Section: Discussionsupporting
confidence: 93%
“…A breakdown of these loops due to advanced disease or surgical procedure might be responsible for the breakdown of multifractal complexity into monofractal [7][8][9]11]. However, the exact electrophysiological mechanisms causing such postoperative dysregulation remain unclear [14,15,33]. Significantly higher postoperative values of Δh parameter in our study indicate a considerable postoperative increase in sympathetic activity, which is in agreement with previous works describing sympathetic augmentation after surgical intervention [1,14,15,34].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The decrease of DFA indexes may be associated with greater likelihood of cardiac events and mortality. Ksela et al (37) observed a greater decline of nonlinear indexes (DFA) in patients who developed cardiac arrhythmias in the postoperative period compared with those who maintained stable sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%